Penerapan Immersive Virtual Learning terhadap Pemahaman Konsep Perubahan Iklim dan Keterampilan Proses Berpikir - Asita Al Mufida; Ari Widodo; Rini Solihat (Postgraduate, University of Mataram, 2022)
problem of climate change is currently a problem that worries people around the world. Education is considered one way to solve this problem. However, the material on climate change is challenging to understand because the concepts contained in it are complex and require good thinking skills. Therefore, learning is needed that can facilitate this. Immersive Virtual Learning (IVL) analyzes the results of its application to students' understanding and thinking process abilities. The use of a pre-post control group design involving 59 junior high school students showed student learning outcomes in the class were significantly different from the control class. The understanding of the concept of treatment students is better than the control class students. The same results are also shown in the results of data analysis related to thinking skills in the two classes. It is hoped that there will be further research related to IVL to get better learning outcomes